Attenuation of Multiple Vibrio parahaemolyticus Virulence Factors by Citral - Sun, Yi; Guo, Du; Hua, Zi; Sun, Huihui; Zheng, Zhanwen; Xia, Xiaodong; Shi, Chao (Frontiers in Microbiology, 2019)
Citral was known as a widely used food additive with antimicrobial activity; however, whether it can be a potential therapy for controlling bacterial virulence with less risk of antimicrobial resistance remains to be investigated. Herein, we demonstrated that Vibrio parahaemolyticus virulence factors that contribute to infection were effectively inhibited to different degrees by sub-inhibitory concentrations (3.125, 6.25, and 12.5 μg/ml) of citral. Citral exerted strong inhibition of autoinducer-2 production and adhesion to Caco-2 cells. Biofilm formation of V. parahaemolyticus was effectively decreased by citral at 30°C and 20°C. Moreover, citral repressed the transcription of genes related to flagella biosynthesis, biofilm formation, type III secretion effectors, and antibiotic resistance, as well as genes contributing to the regulation of quorum sensing and toxin production. Therefore, citral could effectively attenuate multiple virulence properties of V. parahaemolyticus, and its effect on in vivo infection by V. parahaemolyticus needs further investigation.